Preemergent Liverwort Control by Organic Mulching in Containerized Ornamental Production - Manjot Kaur Sidhu; Sushila Chaudhari; Roberto G. Lopez; Eric L. Patterson; Debalina Saha (Horticulturae)
Liverwort (Marchantia polymorpha) competes for resources within containers, resulting in a reduction in the quality and market value of ornamentals. Therefore, the objective of this study was (1) to assess the impact of different mulch types, depths, and their moisture-holding-capacity on liverwort control and (2) to quantify if phytotoxicities develop on ornamental plants due to the mulches. The percent water retention of four different organic mulches [rice hull (RH), cocoa hull (CH), pine bark (PB), or red hardwood (HW)] was determined in a laboratory experiment. In a greenhouse experiment, the Hosta plantaginea (Plantain Lily) varieties ‘Curly Fries’ and ‘Pandora’s Box’ were mulched with either RH, HW, CH, or PB at a depth of 0.63, 1.27, 2.54, or 5.08 cm. Liverwort thalli coverage on the container surface was visually estimated bi-weekly, and the fresh weight of the thalli was recorded at the end of the experiment. The results indicated that CH mulch retained the highest amount of moisture (86%). The RH and HW mulches, at depths of 1.27 cm or more, provided excellent (>80%) liverwort control in ‘Curly Fries’. All mulches at depths of 1.27 cm or more showed excellent (100%) liverwort control for ‘Pandora’s Box’. Overall, RH and PB mulches at all depths provided excellent liverwort control and no reduction in the growth of ‘Curly Fries’ and ‘Pandora’s Box’.